Computação Ubíqua Aplicada à Acessibilidade - Tavares, João; Barbosa, Jorge; Costa, Cristiano; Yamin, Adenauer; Real, Rodrigo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
This paper presents a model designed to provide ubiquitous accessibility. The project supports accessibility for People With Disability (PWD) and elderly in various situations of their everyday life. Offering context awareness, user profiles and trails management, the model is a base for applying assistive technologies that fulfills accessibility needs. Moreover, in the proposed model, we devised an ontology. Besides the benefits of intrinsic semantic representation, the use of an ontology fosters future integration with others solutions. We also present a case study based on a prototype, which was developed to evaluate the model. This assessment used a smart wheelchair, operated by a paraplegic person, which is under development at University of the Sinos Valley (Unisinos).